Analisa Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Pada Pelaku Usaha Bisnis Online - Kurnianto, Daniel; Iskandar, Deni (Jurnal Akuntansi, 2023)
The purpose of this study is to find out how taxpayer awareness, understanding of taxation, and knowledge of taxation affect taxpayer compliance. The independent variables of this study are tax knowledge, understanding of taxation, and taxpayer awareness. In addition, taxpayer compliance is the dependent variable in this study. The population and sample of this study are online business people in Jakarta. The study used a purposive sampling strategy to collect data by sending questionnaires to people who had online businesses. A total of 92 respondents were obtained. This study used IBM SPSS 25 for multiple linear analysis in this study. The findings of this study show that simultaneously the independent variable has a positive and significant effect on the dependent variable. The variable of tax understanding and the variable of taxpayer awareness both have a positive effect on taxpayer compliance, while the variable of tax knowledge does not have a significant effect on taxpayer compliance Keywords : tax knowledge, tax understanding, taxpayer awareness, taxpayer compliance, online business